Anglicism in Speech of Emmanuel Macron and François Hollande - Marice; Isda Pramuniati; Mahriyuni; William Hutapea (Universitas Pendidikan Ganesha, 2023)
Lexical Anglicism is the use of English terms or expressions. Phonetic Anglicism is a mispronunciation, such as pronouncing zoo as [zo]. This study aims to analyze how Emmanuel Macron and François Hollande use Anglicism in their speeches. A loanword that is English in the form, including spelling, sound, and morphology — that's what we call an